1999
DOI: 10.1111/j.1365-2621.1999.tb15078.x
|View full text |Cite
|
Sign up to set email alerts
|

High Pressure Inactivation Kinetics of Saccharomyces cerevisiae Ascospores in Orange and Apple Juices

Abstract: High pressure inactivation kinetics (D and z values) of Saccharomyces cerevisiae ascospores were determined in fruit juices and a model juice buffer at pH 3.5 to 5.0. Approximately 0.5 to 1.0 3 10 6 ascospores/mL were pressurized at 300 to 500 MPa in juice or buffer. D-values ranged from 8 sec to 10.8 min at 500 and 300 MPa, respectively. The range for z-values was 115 to 121 MPa. No differences (P$0.05) in D (at constant pressure) or z-values among buffers or juices at any pH were determined, indicating littl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0
4

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(56 citation statements)
references
References 9 publications
1
49
0
4
Order By: Relevance
“…First-order kinetics have been used to calculate pressure death-time data for bacteria and yeasts previously (10,11,48). However, for Bacillus species (16,28) and for E. coli (15), it was shown that pressure inactivation curves may exhibit a pronounced shoulder and tailing.…”
Section: Discussionmentioning
confidence: 99%
“…First-order kinetics have been used to calculate pressure death-time data for bacteria and yeasts previously (10,11,48). However, for Bacillus species (16,28) and for E. coli (15), it was shown that pressure inactivation curves may exhibit a pronounced shoulder and tailing.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrences of outbreaks of infections of Escherichia coli O157:H7 and other pathogens due to unpasteurized fruit juices have prompted the United States Food Drug Administration (USFDA) to ratify the Federal Juice Hazard Analysis Critical Control Point (HACCP) that compels manufacturers to subject juice products to a processing step or combinations of processes capable of reducing a population of a target pathogen by 5 log cycles (FR 2001;Goodrich, Schneider, & Parish, 2005). Spoilage microorganisms in juices include yeast species which produce metabolites that negatively affect sensory quality (Basak, Ramaswamy, & Piette, 2002;Zook, Parish, Braddock, & Balaban, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Most spoilages of fruit juice are caused by yeast and mold, because the germination of bacterial spores is inhibited at the pH of fruit juice (30). Shimoda et al (27) have reported that the inactivation temperature of Saccharomyces cerevisiae was reduced by about 30°C under high-pressure carbonation.…”
mentioning
confidence: 99%